Microtubule-Associated Protein 1 Light Chain 3B, (LC3B) Is Necessary to Maintain Lipid-Mediated Homeostasis in the Retinal Pigment Epithelium - Dhingra, Anuradha; Bell, Brent A.; Peachey, Neal S.; Daniele, Lauren L.; Reyes-Reveles, Juan; Sharp, Rachel C.; Jun, Bokkyoo; Bazan, Nicolas G.; Sparrow, Janet R.; Kim, Hye Jin; Philp, Nancy J.; Boesze-Battaglia, Kathleen (Frontiers in Cellular Neuroscience, 2018)
Like other neurons, retinal cells utilize autophagic pathways to maintain cell homeostasis. The mammalian retina relies on heterophagy and selective autophagy to efficiently degrade and metabolize ingested lipids with disruption in autophagy associated degradation contributing to age related retinal disorders. The retinal pigment epithelium (RPE) supports photoreceptor cell renewal by daily phagocytosis of shed photoreceptor outer segments (OS). The daily ingestion of these lipid-rich OS imposes a constant degradative burden on these terminally differentiated cells. These cells rely on Microtubule-Associated Protein 1 Light Chain 3 (LC3) family of proteins for phagocytic clearance of the ingested OS. The LC3 family comprises of three highly homologous members, MAP1LC3A (LC3A), MAP1LC3B (LC3B) and MAP1LC3C (LC3C). The purpose of this study was to determine whether the LC3B isoform plays a specific role in maintaining RPE lipid homeostasis. We examined the RPE and retina of the LC3B-/- mouse as a function of age using in vivo ocular imaging and electroretinography coupled with ex vivo, lipidomic analyses of lipid mediators, assessment of bisretinoids as well as imaging of lipid aggregates. Deletion of LC3B resulted in defects within the RPE including increased phagosome accumulation, decreased fatty acid oxidation and a subsequent increase in RPE and sub-RPE lipid deposits. Age-dependent RPE changes included elevated levels of oxidized cholesterol, deposition of 4-HNE lipid peroxidation products, bisretinoid lipofuscin accumulation, and subretinal migration of microglia, collectively likely contributing to loss of retinal function. These observations are consistent with a critical role for LC3B-dependent processes in the maintenance of normal lipid homeostasis in the aging RPE, and suggest that LC3 isoform specific disruption in autophagic processes contribute to AMD-like pathogenesis.